Investigation of contact pendants C-2C-3, YC120-2CS150 and YC150-2CS150 types - Kanaevski, M.; Roek, A.; Bialonj, A. (Science and Transport Progress, 2008)
The paper presents the OCL tests that have been carried out from the year1994 inthe PKP’s infrastructure, and which aim at construction of an OCL adapted for high speeds. Described were following OCL 2C120-2C-3 (modernised) and new type YC150-2CS150 and YC120-2C150. The tests showed that new OCL (of YC150-2CS150 and YC120-2C150 type) also enable to run with a speed of200 km/h. It should be noted that probably the speed of 200 km/his not a limit speed for these OCL types.